(untitled) (CIPEEX, 2025)
Ozone therapy is a complementary integrative practice that uses ozone gas (O3) diluted in oxygen (O2) for therapeutic purposes. Since the 18th century, ozone therapy has been applied in antibacterial treatments and has recently gained prominence in aesthetic procedures due to its antioxidant and regenerative properties. The recognition and regulation of ozone therapy by the Federal Pharmacy Council (CFF) authorizes pharmacists to practice this technique. METHODOLOGY: This study is a bibliographic review, based on searches in the PUBMED, LILACS and BVS databases, focusing on publications between 2020-2024. RESULTS: In clinical practice, ozone therapy has been consolidated in aesthetic treatments such as acne, cellulite, stretch marks, and skin aging. Specialized literature has shown that, in addition to its antioxidant functions, ozone increases collagen synthesis and blood flow, allowing for proper tissue regeneration and improved skin quality. Pharmacists play a particularly important role in maintaining the safety and efficacy of procedures, as they have technical knowledge of how ozone is produced and how the therapy is applied. CONCLUSION: Ozone therapy is an effective and innovative technique for aesthetic treatments, with proven benefits in improving skin quality and tissue regeneration. Therefore, the professional pharmacist is of essential importance in this area, providing quality and safety to the client. In addition, the guidance provided by the pharmacist on post-procedure care is essential to ensure that patients follow the best practices to maintain and enhance the effects of the treatment.BIBLIOGRAPHICAL REFERENCESBAÍA, L. Cartilha de farmácia estética e ozonioterapia. Conselho Regional De Farmácia do Estado de Goiás, Goiânia, 2020 Disponível em: lt;https://crfgo.org.br/img/cartilha_farmacia_estetica.pdfgt;. Acesso em: 22 set.2024. GAMBÔA R. F, SANTOS J. A. Uso da ozônioterapia na estética | Recima21 - Revista Científica Multidisciplinar - ISSN 2675-6218. recima21.com.br, 29 maio 2023. Disponível em: lt;https://recima21.com.br/index.php/recima21/article/view/3277/2358gt; Acesso 25 set. 2024.MATOS, E. L. E J. Ozonioterapia: Um negócio lucrativo para Farmacêuticos. Disponível em: lt;https://ictq.com.br/guia-de-carreiras/2755-atuacao-do-farmaceutico-com-ozonioterapiagt;. Acesso em: 23 set.2024.PÁEZ, T. T. et al. Ozonioterapia e seus aspectos controvertidos: Diálogos Interdisciplinares, v. 9, n. 5, p. 1–21, 4 jun. 2020 Disponível em: lt; https://revistas.brazcubas.br/index.php/dialogos/article/view/950gt;. Acesso em: 22 set.2024. DE OLIVEIRA, Thaís Alves et al. Ozonioterapia: uma prática inovadora na área farmacêutica. Caderno Pedagógico, v. 21, n. 6, p. e4991-e4991, 2024.